Utilization of Probiotic Bacillus sp. and Staphylococcus sp. In Tilapia (Oreochromis niloticus) Seed Maintenance Media for Resistance to Aeromonas hydrophila - Cindytia Prastari; Henri Sinaga (Berkala Perikanan Terubuk, 2021)
This research aimed to determine the benefits of giving the multispecies probiotic Bacillus sp. and Staphylococcus sp. That appropriate to the media so that treatment can improve survival rate of Tilapia (Oreochromis niloticus) immune to Aeromonas hydrophila. The method used in this research was an experimental method of Completely Randomized Design (CRD) with four treatments and three replications. The treatments were A (without the addition of probiotics Bacillus sp. and Staphylococcus sp. and without addition of Aeromonas hydrophila (negative control), B (without the addition of probiotics Bacillus sp. and Staphylococcus sp. and administration of Aeromonas hydrophila 104 CFU/ml (positive control),  C (addition of probiotic Bacillus sp. 104 CFU/ml and Staphylococcus sp. 104 CFU/ml given daily and addition of Aeromonas hydrophila 104 CFU/ml) and D (addition of probiotic Bacillus sp. 104 CFU/ml and Staphylococcus sp. 104 CFU/ml is given everydays and the addition of Aeromonas hydrophila 104 CFU/ml). The parameters observed were the survival rate of the test fish during the maintenance period of biomass growth, Feed Conversion Ratio (FCR), leukocyte differential, phagocytic index and water quality. The results showed that the probiotic treatment D (Bacillus sp. 104 CFU/ml and Staphylococcus sp. 104 CFU/ml) on tilapia seed rearingwith addition of every three days was the bestresulted in the highest survival of 93.33%, the proportion of monocytes 40% and phagocytic activity of 78.5% compared to treatments A, B and C.